Flexible transparent conductive films combining flexographic printed silver grids with CNT coating. (13th January 2016) - Mo, Lixin; Ran, Jun; Yang, Li; Fang, Yi; Zhai, Qingbin; Li, Luhai
Abstract: A high-performance ITO-free transparent conductive film (TCF) has been made by combining high resolution Ag grids with a carbon nanotube (CNT) coating. Ag grids printed with flexography have a 20 μ m line width at a grid interval of 400 μ m. The Ag grid/CNT hybrid film exhibits excellent overall performance, with a typical sheet resistance of 14.8 Ω/□ and 82.6% light transmittance at room temperature. This means a 23.98% reduction in sheet resistance and only 2.52% loss in transmittance compared to a pure Ag grid film. Analysis indicates that filling areas between the Ag grids and interconnecting the silver nanoparticles with the CNT coating are the primary reasons for the significantly improved conductivity of the hybrid film that also exhibits excellent flexibility and mechanical strength compared to an ITO film. The hybrid film may fully satisfy the requirements of different applications, e.g. use as the anode of polymer solar cells (PSCs). The J – V curve shows that the power conversion efficiency (PCE) of the PSCs using the Ag grid/CNT hybrid anode is 0.61%, which is 24.5% higher than that of the pure Ag grids with a PCE of 0.49%. Further investigations to improve the performance of the solar cells based on the printed hybrid TCFs are ongoing.